2022
DOI: 10.1111/jace.18606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aqueous solution pH on network structure of corrosion‐induced surface layers of boroaluminosilicate glass

Abstract: Understanding of the long‐term stability of vitrified nuclear waste glass is critical to its safe storage, but knowledge gaps remain regarding the corrosion mechanism, especially with respect to surface alteration layers whose presence changes the observed corrosion rates. Here, we report the aqueous corrosion of a model boroaluminosilicate glass at ground water relevant pHs as investigated by vibrational spectroscopy to understand the network structure of the alteration layer that we hypothesize controls the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…For instance, Damodaran et al (2022) reported apparent diffusion coefficient of B within ISG gel of the order of 10 -21 m 2 .s -148 . The speciation of B in gel is not well known, although a former study suggested that B is likely under aqueous form 49 .…”
Section: Residual Ratementioning
confidence: 99%
“…For instance, Damodaran et al (2022) reported apparent diffusion coefficient of B within ISG gel of the order of 10 -21 m 2 .s -148 . The speciation of B in gel is not well known, although a former study suggested that B is likely under aqueous form 49 .…”
Section: Residual Ratementioning
confidence: 99%